Bacterial resistance and immunological profiles in HIV-infected and non-infected patients at Mbouda AD LUCEM Hospital in Cameroon. Issue 3 (May 2017) - Marbou, Wiliane J.T.; Kuete, Victor
Summary: This study investigated the variations in some cells of the immune system, as well as the antibiotic resistance of the bacteria responsible for enteric infections among HIV+ patients compared to HIV− patients in Mbouda AD LUCEM Hospital, Cameroon. A cross-sectional study was performed from September 2014 to February 2015 in 67 human immunodeficiency virus (HIV)-seropositive (HIV+) and 37 HIV-seronegative (HIV−) patients. Blood collected from these patients was used to perform cluster of differentiation 4 (CD4) and cluster of differentiation 8 (CD8) lymphocyte blood counts and a white blood cell count, as well as to measure C-reactive protein (CRP) blood by flow cytometry and perform optical and immuno-turbidimetric detection. Enteric bacteria were isolated from the stool of patients, and their antibiotic susceptibility profiles were determined using agar diffusion methods. The results showed that Escherichia coli was the main pathogenic bacteria in the digestive tracts of HIV+ (85.3%) and HIV− (81.1%) patients, and infections with Klebsiella sp. were also predominant among HIV− patients (29.4%). Resistance of Klebsiella sp. to ceftriaxone (CRO; P  = 0.001), gentamicin (GEN; P  = 0.005), chloramphenicol (CHL; P  = 0.0004), ciprofloxacin (CIP; P  = 0.005) and doxycycline (DOX; P  < 0.0001) was significantly higher in HIV+ patients than in HIV− patients. Enterobacter sp. showed high resistance to GEN ( P  = 0.009) and CIP ( P  = 0.001) in HIV+ patients compared to HIV− patients. Citrobacter sp. was resistant to GEN ( P  = 0.009) in HIV+ patients compared to HIV− patients. Salmonella sp. showed high resistance to CHL ( P  < 0.0001) and DOX ( P  < 0.0001) in HIV+ patients compared to HIV− patients. Resistance of Serratia sp. to AMO ( P  = 0.005), AMC ( P  = 0.005) and CHL ( P  = 0.005) was significantly higher in HIV+ patients than in HIV− patients. Lymphopenia was higher in HIV+ patients (36.8%) than in HIV− patients (2.7%). In 45.9% of the HIV− patients, the CRP rate was higher than 6 mg/L compared to 16.2% in HIV+ patients. In general, bacterial multi-drug resistance in HIV+ patients (79.4%) was significantly higher ( P  < 0.0001) than in HIV− patients (29.7%). The present study revealed that the resistance profiles of bacteria should be considered in HIV-infected patients to improve their health care.